INFLUENCE OF TAXES ON STIMULATION OF INVESTMENT ACTIVITY - Bechko P. K; Barabash L. V; Bondarenko N. V.; Vlasyuk S. A.; Hmyria Viktoriia Petrivna (Scientific Journal of Pedagogy and Economics, 2019)
The search for ways and methods of stimulation of investment activity of business entities of Ukraine is one of the burning issues, especially in agriculture. From this perspective, special attention should be paid to tax tools to stimulate investment activities, which include tax preferences, tax rates, special tax regimes and temporary means of influence. After considering each of the mentioned ways of optimization, it was investigated that providing tax preferences in order to stimulate investment activity has to be direct in nature, however, tax preferences in Ukraine do not give the expected result since the efficiency of their functioning is rather low in spite of their significant number. Tax rates constitute an active and efficient element in the increase of investment activity. However, their misuse provokes an increase of the level of the tax burden that slows the increase of the volumes of the technological production. A similar characteristic can be also applied to an investment credit, the use of which, in combination with tax rates, gives a good result, provided that the progressive scale of rates but not linear or low-progressive (as in Ukraine) is used. Therefore, the analysis of the results of the activities of enterprises of Ukraine showed, firstly, a low level of growth in the volume of commissioning of capital assets, which in 2017 amounted to only 2.6% of the level of 2016, and an overall reduction of 8.3 percentage points compared to 2012, and, secondly, a reduction in the volume and pace of investment activity. It should also be noted that the low level of general and investment activity of enterprises, in particular, agricultural ones, also provokes a decrease in the social standard of living. Consequently, the negative trends in the economic environment, which provoked a decrease in the social standards, resulted in a total reduction of the budget revenues and a high level of the budget deficit at all levels. That is why, a harmony of the tools of influence and social aims is necessary to activate the investment activity of business entities, especially in the agricultural sector.